As mídias e as mediações da experiência religiosa - Rodrigues, Luís Miguel Figueiredo (Revista Eclesiástica Brasileira, 2020)
Este artigo discute a possibilidade de as mídias digitais poderem mediar também a experiência religiosas, estando, assim, ao serviço da evangelização. Segue de perto o pensamento de Bernard Lonergan para, em articulação com a cultura digital, se perceber como a autotranscedência do sujeito pode ocorrer na sociedade rede (Manuel Castells) e no espaço do saber (Pierre Lévy). Abstract: This paper examines the possibility that digital media may also mediate religious experience, at the service of evangelization. It closely follows the thinking of Bernard Lonergan to, in articulation with the digital culture, to perceive how the self-transcendence of the subject can occur in the network society (Manuel Castells) and in the space of knowledge (Pierre Lévy). Keywords: Digital media; Bernard Lonergan; Self-transcendence; Evangelization.